A method for measuring the continuous dispersion spectrum of nonlinear refraction coefficients of materials. (1st January 2018) - Deng, Zhichao; Wang, Jin; Ye, Qing; Sun, Tengqian; Liu, Shike; Zhou, Wenyuan; Zhang, Chunping; Mei, Jianchun; Tian, Jianguo
Highlights: A method to measure the dispersion of nonlinear refraction coefficients is proposed. The method is based on the complex refractive index dispersion measurements. The RI at wavelengths far from the nonlinear range illustrates the thermal effects. A large nonlinear refraction coefficient of methyl-red-doped sample was observed. Abstract: In this paper, a method for measuring the continuous dispersion spectrum of nonlinear refraction coefficients of materials based on complex refractive index dispersion (CRID) measurement is proposed. This method involves measuring internal reflection spectra with a lab-made apparatus. From the determined CRIDs of a material with and without exciting light, the changes in refractive index over a wide spectral range can be obtained, from which the nonlinear refraction coefficients can be deduced. In addition, the RI changes at wavelengths far from the nonlinear range can be used to monitor the thermal effects. In this study, a methyl-red-doped poly(methyl methacrylate) (MR-PMMA) sample was investigated. A large nonlinear refraction coefficient on the order of 10 −1  cm 2 /W was observed. The results also show that the absolute value of nonlinear refraction coefficient of the MR-PMMA sample decreases with the increase of excitation intensity. Consequently, this study provides a powerful approach that has the potential to be applied in the study of the nonlinear properties of materials.